Short-range inverse-square law experiment in space - Strayer, Donald M.; Paik, Ho Jung; Moody, M. Vol (Физика низких температур, 2003)
The objective of ISLES (inverse-square law experiment in space) is to perform a null test of Newton`s law on the ISS with a resolution of one part in 10⁵ at ranges from 100 mm to 1 mm. ISLES will be sensitive enough to detect axions with the strongest allowed coupling and to test the string-theory prediction with R≥ 5 mm. To accomplish these goals on the rather noisy International Space Station, the experiment is set up to provide immunity from the vibrations and other common-mode accelerations. The measures to be applied for reducing the effects of disturbances will be described in this presentation. As designed, the experiment will be cooled to less than 2 K in NASA`s low temperature facility the LTMPF, allowing superconducting magnetic levitation in microgravity to obtain very soft, low-loss suspension of the test masses. The low-damping magnetic levitation, combined with a low-noise SQUID, leads to extremely low intrinsic noise in the detector. To minimize Newtonian errors, ISLES employs a near-null source of gravity, a circular disk of large diameter-to-thickness ratio. Two test masses, also disk-shaped, are suspended on the two sides of the source mass at a distance of 100 mm to 1 mm. The signal is detected by a superconducting differential accelerometer, making a highly sensitive sensor of the gravity force generated by the source mass.